Incorporation of Palm Fiber to Enhance the Mechanical Properties of Epoxy - Hussein, Samah M (Iraqi Journal of Science, 2020)
In the recent years, the work in composite industry needed new ecofriendly resources to improve the original properties of current materials. Many researches attempted to find alternative additives to be used with the current systems which provide a new material that is environmentally friendly and has better performance than the synthetic counterparts. This paper presents the study of mechanical characteristics, including bending, impact, tensile and hardness tests, of date palm fiber (DPF)/ epoxy composite. The composite plate was constructed by hand-layup technique. The filler content values (wt %) were 5%, 10%, 15% and 20%. Young's modulus, impact strength and hardness were shown to be increased with increasing fiber content. Tensile strength was increased only using 5% and 10%, whereas it was decreased using fiber content.